2017
DOI: 10.2147/opth.s132184
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis incidence in Jichi Medical University Hospital, Japan, during 2011-2015

Abstract: PurposeTo investigate uveitis incidence of new patients who visited Jichi Medical University Hospital, Tochigi, north of Tokyo, during 2011–2015, and to compare the results with previously reported data from other facilities.MethodsWe retrospectively analyzed clinical records of new patients with uveitis from April 2011 to March 2015 and compared the uveitis incidence with those from other hospitals.ResultsA total of 502 patients were enrolled in the study; definite diagnoses were made in 262 patients (52.2%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In China the highest percentage of panuveitis is reported [18], due to the high incidence of both VKH and Bechet disease (accounting respectively for 29-30% of all uveitis) [19]. In Japan VKH was considered the first cause of uveitis [18,20], but differences in etiology of uveitis are being observed over time [21], and in most recent studies it is reported as the second cause of uveitis (7% of all uveitis) after sarcoidosis [22,23]. On the other hand, higher VKH rates than expected are being recorded in South America: in Chile [24] VKH has been reported as the most frequent cause of uveitis, accounting for 17,2% of all uveitis, and in Argentina as the second cause after toxoplasmosis, accounting for 16.7% of all uveitis [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China the highest percentage of panuveitis is reported [18], due to the high incidence of both VKH and Bechet disease (accounting respectively for 29-30% of all uveitis) [19]. In Japan VKH was considered the first cause of uveitis [18,20], but differences in etiology of uveitis are being observed over time [21], and in most recent studies it is reported as the second cause of uveitis (7% of all uveitis) after sarcoidosis [22,23]. On the other hand, higher VKH rates than expected are being recorded in South America: in Chile [24] VKH has been reported as the most frequent cause of uveitis, accounting for 17,2% of all uveitis, and in Argentina as the second cause after toxoplasmosis, accounting for 16.7% of all uveitis [18].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, neurological signs and dysacousia are quite common (74-76%) among Japanese patients [23,28], while intertegumentary signs are more often seen in Chinese patients (39-41%) [29]. When looking at ocular manifestations, studies conducted on South American patients are concordant in rating a optic disc swelling occurrence significantly lower than in Asian patients (8,6% -9% versus 50-73%, respectively) [26][27][28][29][30] Giordano et al) [26,30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared with patients before 2010, recent patients in Singapore showed a higher percentage of infectious uveitis [26]. Studies in Japan have revealed that 35-63% of uveitis cases were noninfectious, and 31-50% were idiopathic [7,[27][28][29][30][31][32]. These studies have also demonstrated that the patterns and specific entities of uveitis, including endophthalmitis, sarcoidosis, Bechet's disease, VKH disease, and anterior uveitis, have changed with time.…”
Section: Epidemiology and Distribution Of Etiologiesmentioning
confidence: 99%